IMPLEMENTATION OF DECISION SUPPORT SYSTEMS IN THE SELECTION OF E-COMMERCE MARKETPLACES FOR MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) - Darwin Darwin; Sukiman Sukiman; Sugianto Sugianto (Proceeding International Seminar of Islamic Studies, 2022)
MSME business actors face quite severe challenges related to business development, including the small use of information technology, even though the use of IT can increase business transformation through the speed, accuracy and efficiency of exchanging large amounts of information, especially during the COVID-19 pandemic which is still ongoing. takes place from 2019 to the present. Therefore, the role of technology is needed in encouraging the success of MSME actors to expand market access through the use of information technology based on the E-Commerce Marketplace which can be used as a modern marketing communication medium. MSME actors must make a decision to use E-Commerce that best suits their needs and circumstances. Decision-making is a process of selecting alternative actions to achieve certain goals or objectives. To assist in the decision-making process, currently we can use information technology in the form of a Decision Support System. Many approach methods that can be used in Decision Support Systems. One method that can be used is the Weighted Aggregated Sum Product Assessment (WASPAS) method. Where this research aims to be a recommendation for Micro, Small and Medium Enterprises (MSMEs)in the selection of an e-commerce marketplace as a marketing medium for MSMEs products that best suits their needs. So that by implementing this SPK, it is able to help MSMEs actors determine the most ideal marketing location according to their needssKeywords:DSS, Marketplace, E-Commerce, Actors, MSMEs